The Better I Can Be: In Defence of Human Enhancement for a New Genetic Equality - Carapeto Raposo, Vera (Canadian Journal of Bioethics / Revue canadienne de bioéthique, 2022)
The main objection to genetic enhancement is that it will create a “genetic apartheid,” deepening existing inequalities. This paper offers considerations that can weaken the inequality argument against genetic enhancement. First, I question the dichotomy of treatment versus enhancement since the differences between the two are unclear. Second, I argue that human enhancement is part of human nature and that there is no sound reason to accept it in other domains while rejecting it in genetics. The paper also demonstrates that inequality is present in every dimension of society, that “God-given” genetics is profoundly unequal, and that genetic enhancement can operate as a mechanism by which a new genetic equality can be achieved. However, the paper underlines that genetic equality is not, per se, a value to which we ought to aspire if it leads us to a uniform community of downsized human beings. Genetic equality is only valuable if it enhances humankind in general.